Bullying and Suicide in Adolescents - yusfina himayanti; Husnuzzia Urrahmah (PROFESSIONAL HEALTH JOURNAL, 2024)
The purpose of this study was to explore the experiences of students who experienced bullying resulting in suicide attempts. This research is a qualitative study with an interpretative phenomenology approach and data analysis using science (interpretative phenomenological Analysis). The resulting theme was based on the results of research between feeling hurt because of experiencing bullying by peers. . The results of this study show that perceived bullying is a trigger that causes. Teen makes suicide attempt